KONSEPSI ISLAM TENTANG PEMBANGUNAN - Sagir, Akhmad (UIN Antasari Banjarmasin, 2012)
Islam is a religion that teaches the balance of understanding, thinking and implementation of living in the world and in the hereafter. Included in the category is development in its broadest sense, both physical and non-physical or mental. Even further than that, Islam also requires its adherents to develop and foster spirituality which is believed as potential seeds of every human being. Because it is agreed that human being as the creature not only consists of physical dimension, but also the spiritual one. In Islam, the spiritual dimension is very influential on the development of the characters that affect physical development.